Through the agrarian lens: an extended approach to reflexive photography with farmers. Issue 4 (2nd October 2018) - Stotten, Rike
Abstract : This paper presents the documentation of the application of a reflexive photography approach and aims to elaborate its evaluation process. Farmers in Central Switzerland were first asked to take photos, after which interviews and group discussions were conducted with the farmers to explore their landscape perception. The reflexive photography method was applied in two steps. First, as the basis for the in-depth interviews evaluated with qualitative content analysis according to Philip Mayring, and second as the basis for group discussions evaluated with the documentary method according to Ralf Bohnsack. The paper's goal is to provide deeper insight into the process of conducting a reflexive photography approach in rural studies.